Chronic inhibition of nitric oxide synthase augments the ACTH response to exercise - Jankord, Ryan (American Physiological Society, 2009)
Exercise can activate the hypothalamo-pituitary-adrenocortical (HPA) axis, and regular exercise training can impact how the HPA axis responds to stress. The mechanism by which acute exercise induces HPA activity is unclear. Therefore, the purpose of this study was to test the hypothesis that nitric oxide modulates the neuroendocrine component of the HPA axis during exercise. Female Yucatan miniature swine were treated with N-nitro-l-arginine methyl ester (l-NAME) to test the effect of chronic nitric oxide synthase (NOS) inhibition on the ACTH response to exercise. In addition, we tested the effect of NOS inhibition on blood flow to tissues of the HPA axis and report the effects of handling and treadmill exercise on the plasma concentrations of ACTH and cortisol. Chronic NOS inhibition decreased plasma NO(x) levels by 44%, increased mean arterial blood pressure by 46%, and increased expression of neuronal NOS in carotid arteries. Vascular conductance was decreased in the frontal cortex, the hypothalamus, and the adrenal gland. Chronic NOS inhibition exaggerated the ACTH response to exercise. In contrast, chronic NOS inhibition decreased the ACTH response to restraint, suggesting that the role of NO in modulating HPA activity is stressor dependent. These results demonstrate that NOS activity modulates the response of the neuroendocrine component of the HPA axis during exercise stress.